Effects of Artificial Intelligence on Cognitive Domain of Tertiary Institutions Students in Rivers State, Nigeria - Udoinyang, Nathan; Rowland Chimezunum Chukwu; Chidinma Esther Ogbonnaya-Ngwu (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study investigated the effects of artificial intelligence (AI) on the cognitive domain of tertiary institution students in Rivers State, Nigeria, aiming to assess AI tools' usage and impact on cognitive skills and learning outcomes and identify challenges and opportunities of AI adoption. Employing a survey research design, the study collected data from 1500 respondents (students and lecturers) across Rivers State's tertiary institutions using a structured questionnaire. Findings revealed significant AI integration, enhancing personalized learning, cognitive skills like analytical thinking and problem-solving, and learning outcomes. AI's management of cognitive load and scaffolding of learning aligned with Cognitive Load Theory and Constructivist Learning Theory. Challenges included infrastructure limitations, training needs, equity concerns, and data privacy risks, while opportunities encompassed enhanced personalization, efficiency, innovative learning tools, and future-ready skills. The study concluded that AI has potential in transforming Rivers State's tertiary institutions' students' education by emphasizing careful implementation and strategic investments. Thus, it is recommended that the government invest in AI infrastructure, teacher training, addressing equity and access concerns, enhancing data security, promoting personalized learning, monitoring AI impact and ethics, and engaging educational stakeholders for effective AI integration in Rivers State.